A New Ratio-Metric pH Probe, “ThiAKS Green” for Live-Cell pH Measurements - Ali Akyol; Doruk Baykal; Akın Akdağ; Özge Şensoy; Çağdaş Devrim Son (Photonic Sensors, 2022)
Abstract Deviation of the H+ concentration from optimum values within the organelles is closely associated with irregular cellular functions that cause the onset of various diseases. Therefore, determining subcellular pH values in live cells and tissues is valuable for diagnostic purposes. In this study, we report a novel ratiometric fluorescence probe 1H-pyrazole-3-carboxylic acid, 4-(benzo[d]thiazol-2-yl)-3-(2,4-dihydroxy-3-methylphenyl)-1H-pyrazole-5-carboxylicacid4-(2-benz othiazolyl)-5-(2,4-dihydroxy-3-methylphenyl), to which we will refer as ThiAKS Green (Thiazole AKyol shifting green), that is pH sensitive. The results presented here show that the probe can penetrate the cell membrane in less than 30 minutes and does not show any detectable toxicity. The measured color shifts up on pH change are linear and most significant around physiological pH (pKa=7.45), thus making this probe suitable for live-cell imaging and intracellular pH measurements. During the long-incubation periods following the application of the probe and the fluorescent microscopy measurements, it shows stable properties and is easy to detect in live cells. In conclusion, the results suggest that ThiAKS Green can be used to obtain precise information on the H+ distribution at various compartments of the live cells.